2015
DOI: 10.1037/a0038370
|View full text |Cite
|
Sign up to set email alerts
|

Personality dimensions and their behavioral correlates in wild Virunga mountain gorillas (Gorilla beringei beringei).

Abstract: Studies of animal personality improve our understanding of individual variation in measures of life history and fitness, such as health and reproductive success. Using a 54 trait personality questionnaire developed for studying great apes and other nonhuman primates, we obtained ratings on 116 wild mountain gorillas (Gorilla beringei beringei) monitored by the Dian Fossey Gorilla Fund's Karisoke Research Center in Rwanda. There were 8 raters who each had more than 1.5 years of working experience with the subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 110 publications
(260 reference statements)
9
96
0
Order By: Relevance
“…This may be more difficult for species that are taxonomically distant from humans; however, at least in primates, the structures derived using behavioral measures and ratings are often highly similar (compare, for example, Table 3 in Neumann et al, 2013 and Table S6 in Adams et al, 2015 or Table 6 in Morton et al, 2013 and Table 3 in Uher & Visalberghi, 2016). Moreover, construct validation typically is post-hoc without predictions of the expected correlations (but see Eckardt et al, 2015 and. We thus urge future researchers to a priori consider what correlations one should and should not expect based on the functions of these behaviors in the species of interest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be more difficult for species that are taxonomically distant from humans; however, at least in primates, the structures derived using behavioral measures and ratings are often highly similar (compare, for example, Table 3 in Neumann et al, 2013 and Table S6 in Adams et al, 2015 or Table 6 in Morton et al, 2013 and Table 3 in Uher & Visalberghi, 2016). Moreover, construct validation typically is post-hoc without predictions of the expected correlations (but see Eckardt et al, 2015 and. We thus urge future researchers to a priori consider what correlations one should and should not expect based on the functions of these behaviors in the species of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondence of rated components and measured behaviors tends be better in studies on ape personality (Eckardt et al, 2015;Pederson et al, 2005;Freeman et al, 2013). As has been discussed elsewhere (e.g., Uher, 2008;Koski, 2011b), this may be because the rating method depends on the degree to which people can intuitively aggregate the study species' behavior into meaningful categories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have revealed associations between primate personality and measures related to social status [76,77], learning, cognitive performance and information processing [78][79][80][81], and health [82,83].…”
Section: (D) Validitymentioning
confidence: 99%